Ovarian torsion in second trimester of pregnancy: a case report - Ganvir, Priti Pralhad; Bambole, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Torsion of the ovary is the total or partial rotation of the adnexa around its vascular axis or pedicle. Although the exact etiology is unknown, common predisposing factors include moderate size cyst, free mobility and long pedicle. Torsion of ovarian tumors occurred predominantly in the reproductive age group. The majority of the cases presented in pregnant (22.7%) than in non-pregnant (6.1%) women. Here, we report a case of ovarian torsion in second trimester of pregnancy. Ovarian torsion is an urgent gynecological surgery and can occur during pregnancy. Surgical techniques should be considered in the development of the adnexal torsion regardless of the gestational age.